PERSEPSI PENGGUNA VAPE TERHADAP PELAYANAN PRIMA SEBAGAI UPAYA PENINGKATAN MUTU PELAYANAN DI VAPEBOSS RUNGKUT SURABAYA - Muhammad Nasirudin Mushohih; Nailul Ulah Al-Chumairah Machfud (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe the perceptions and satisfaction of vape users towards excellent service at VapeBoss Rungkut Surabaya and to analyze efforts to improve service quality. This research used a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. The informants consisted of vape users, store owner, and staff of VapeBoss Rungkut. The results showed that excellent service at VapeBoss Rungkut has generally been going well, with staff friendliness and professionalism, adequate product knowledge, as well as store comfort and cleanliness receiving positive assessments from most informants. However, there are still several aspects that need to be improved, namely service speed during peak hours, service consistency over time, and approach to beginner customers. The main obstacles faced are limited staff during peak hours and high customer expectations of consistent and personal service. This study recommends adding staff during peak hours, improving staff training programs, and routinely collecting customer feedback for continuous improvement to enhance the quality of excellent service at VapeBoss Rungkut.